(untitled) (Journal of Universal Science Research, 2023)
in the article, the authors consider modern and innovative methods and means of teaching a foreign language, highlighting interactive worksheets. It is this means of organizing the learning activities of students that can be used at different stages of the lesson and respond to various educational tasks